Round robin crystal orientation measurement using EBSD for damage assessment - Masayuki KAMAYA (The Japan Society of Mechanical Engineers, 2016)
Crystal orientations of creep damaged Type 316 stainless steel were measured by 10 organizations using the same specimens, passed in a round robin, in order to investigate the scatter in material damage assessment using the electron backscatter diffraction (EBSD) technique. The measurements were performed according to the EBSD measurement guideline issued by the Society of Material Science, Japan. Two misorientation parameters, the local and intra-grain misorientations, were calculated using mapping data of measured crystal orientations. It was shown that the area averaged local and intra-grain misorientations correlated well with the degree of the inelastic strain caused by the creep damage. Although the area averaged local misorientation showed eminent scatter, the scatter in the area averaged intra-grain misorientation was relatively small. The scatter in the area averaged local misorientation was deduced to be brought about by the error in the crystal orientation measurements. Since the accuracy of the crystal orientation measurement depends on various factors and is difficult to control, the correlation between the degree of the creep damage and the local misorientations obtained by one SEM/EBSD system is difficult to apply to other SEM/EBSD systems. On the other hand, the area averaged intra-grain misorientation is not affected much by the error in the crystal orientation measurements and the values obtained by various organizations using different SEM/EBSD systems were almost the same. It was concluded that the area averaged intra-grain misorientation can be used for measurement of the creep damage (inelastic strain). The empirical relationship between the area averaged intra-grain misorientation and the degree of the creep damage can be shared regardless of the SEM/EBSD system used.